Chemical synthesis and epitaxial growth methods for the preparation of ferroelectric ceramics and thin films - Teixeira, Guilhermina F. [UNESP]; Lustosa, Glauco M.M.M. [UNESP]; Zanetti, Snia M. [UNESP]; Zaghete, Maria A. [UNESP] (My University, 2018)
Ferroelectric materials have constantly attracted scientific interest because of their technological applications. The efficiency of ferroelectrics materials is related to the way they are processed because characteristics such as chemical purity, phase homogeneity, and size and shape of the particles are important in the obtained materials. The conventional solid state reaction is widely used to prepare ferroelectric ceramics; however, this method results in inhomogeneities which negatively affect the properties of ceramics. In order to avoid such processing-related issues and to achieve better characteristics, different chemical techniques have been used to synthesize ferroelectric ceramics. When the focus is ferroelectric films, the development of epitaxial growth methods makes it possible to prepare high-quality single crystal and defect-free ultrathin films. Based on this, this chapter discusses the methods for preparation of ferroelectric materials as ceramics and films with the best characteristics.
Keywords: Chemical solution deposition; Chemical synthesis; Epitaxy; Ferroelectric ceramics; Ferroelectric thin films